2017
DOI: 10.1021/acs.jced.7b00696
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibria in Multicomponent Systems Containing o-Xylene, Di-(2-ethylhexyl)phosphoric Acid, Water, Nitric Acid, and Europium (Gadolinium, Dysprosium) Nitrate at 298.15 K

Abstract: The extraction of europium­(III), dysprosium­(III), and gadolinium­(III) nitrates with di-(2-ethylhexyl) phosphoric acid (D2EHPA) in o-xylene was investigated at 298.15 K. Spectrophotometry and ICP-AES techniques were used for rare earth elements (REE) content determination. The content of nitric acid was measured by acid–base titration. The density of the equilibrium phases was determined. In the case of high content of rare earth element nitrates in the initial aqueous solutions, the third solid phase format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al (2016) reported the formation of gray/white or yellow/white precipitates in REE solvent extraction systems using D2HEPA that could not dissolve in diluents but dissolved by increasing the concentration of D2HEPA . The gel is a formation of REE-extractant molecular chains (polymers) and leads to increased viscosity and phase separation problems that reduces performance and can even stop the process completely. Gel formation can be avoided by decreasing the metal concentration and pH in the feed and increasing the carrier concentration in the membrane phase. , Yurtov and Murashova (2007) observed the formation of gel in the bulk of the organic phase for a lanthanide-D2EHPA system when the concentration ratio of D2HEPA/lanthanide corresponded to the formation of neutral and acid salts . Antico et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2016) reported the formation of gray/white or yellow/white precipitates in REE solvent extraction systems using D2HEPA that could not dissolve in diluents but dissolved by increasing the concentration of D2HEPA . The gel is a formation of REE-extractant molecular chains (polymers) and leads to increased viscosity and phase separation problems that reduces performance and can even stop the process completely. Gel formation can be avoided by decreasing the metal concentration and pH in the feed and increasing the carrier concentration in the membrane phase. , Yurtov and Murashova (2007) observed the formation of gel in the bulk of the organic phase for a lanthanide-D2EHPA system when the concentration ratio of D2HEPA/lanthanide corresponded to the formation of neutral and acid salts . Antico et al.…”
Section: Introductionmentioning
confidence: 99%
“…46−48 Gel formation can be avoided by decreasing the metal concentration and pH in the feed and increasing the carrier concentration in the membrane phase. 10,49 Yurtov and Murashova (2007) observed the formation of gel in the bulk of the organic phase for a lanthanide-D2EHPA system when the concentration ratio of D2HEPA/lanthanide corresponded to the formation of neutral and acid salts. 46 Antico et al (1996) studied the distribution of Y 3+ at different concentrations between acidic chloride solutions and organic solutions of D2EHPA diluted in kerosene.…”
Section: Introductionmentioning
confidence: 99%